PREVALENCE RATE OF PSYCHOGENIC RISK FACTORS AMONG PATIENTS WITH ARTERIAL HYPERTENSION OF VARIOUS DEGREES ACCORDING TO CRITERIA OF EVIDENCE-BASED MEDICINE - B. B. Fishman; I. N. Kochanov; A. I. Horoshevskaja; M. A. Bobyr; D. A. Shamiladze; L. A. Fomenko; V. V. Kostirkina; Yu. O. Yevstyukhina (Столичная издательская компания, 2015)
Aim. To study an interrelation of anxiety and depression with arterial hypertension (HT) of various degrees taking into account gender distinctions.Material and methods. One-stage (cardiology and psychometric screening) epidemiology study was carried out in 1% sample of the Novgorod Region adult population. The program of screening included the standard epidemiological record of HT detection and psychometric testing in 1607 respondents with the Hospital anxiety and depression scale (HADS). Risk calculation was performed by logistical regress model using disagreement criterion (odds ratio).Results. HT prevalence rate was 52.1% among men and 49.8% among women of Novgorod Region. The highest prevalence rate of HT was observed at the age ≥70 years: 88.9% among women and 83.6% among men. Relationship between subclinical and clinical types of the anxiety, depression and HT degrees 2-3 was revealed with some gender peculiar properties. Patients with isolated systolic HT had high association with anxiety and depression irrespective of gender.Conclusion. Revealed relationship between anxiety, depression and HT, especially in patients with HT degree 3, required an interdisciplinary approach to the therapy of this group of patients.